1996
DOI: 10.1088/0953-8984/8/28/004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization studies of Landau level broadening in two-dimensional electron systems

Abstract: We have used a torque magnetometer to measure de Haas - van Alphen oscillations in the magnetization of two-dimensional electrons in GaAs/AlGaAs heterostructures and multiple-quantum-well systems for temperatures ranging from 0.125 K to 4.2 K and in magnetic fields of up to 15 T. Our results indicate that for high magnetic fields the density of states can be described by a series of Lorentzian-broadened Landau levels with a broadening that is independent of the magnetic field, B, and Landau level index, n. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 26 publications
8
71
0
Order By: Relevance
“…We checked that in the density range from 3·10 11 cm −2 to 5·10 11ċ m −2 the low-field level broadening is constant (equal to 0.4 meV for sample GaAs-2). The Lorentzian lineshape of the Landau levels is in the agreement with magnetization measurements of Potts et al [28] on the moderate mobility GaAs-based sample. Generally, the shape of DOS in 2D systems is still debated, with a history of research reviewed, e.g., by Usher et al [2].…”
supporting
confidence: 89%
“…We checked that in the density range from 3·10 11 cm −2 to 5·10 11ċ m −2 the low-field level broadening is constant (equal to 0.4 meV for sample GaAs-2). The Lorentzian lineshape of the Landau levels is in the agreement with magnetization measurements of Potts et al [28] on the moderate mobility GaAs-based sample. Generally, the shape of DOS in 2D systems is still debated, with a history of research reviewed, e.g., by Usher et al [2].…”
supporting
confidence: 89%
“…The susceptibility in graphene related systems is expected to be observed by employing the experimental techniques used for two-dimensional electron systems in semiconductor. (66)(67)(68)(69)(70)(71) 7. Acknowledgments…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al [47,48] modelled magnetocapacitance data using a field-independent Gaussian DOS, but a field-dependent width (Γ ∼ √ B) has also been reported experimentally from dHvA [9] and magnetocapacitance [49] measurements, the latter requiring in addition a constant background DOS. Other experiments though indicate a Lorentzian DOS [50,51]. A more recent theoretical model of Glutsch et al [52] showed that a distorted Gaussian DOS can arise, which depends on LL index.…”
Section: Theory Of the Dhva Effect In 2d Systemsmentioning
confidence: 98%